REFLECTING ON ENGLISH TEACHERS’ TEACHING PHILOSOPHY IN TEACHING EFL AT THE SECONDARY LEVEL - Suci Maharani; Didi Suherdi; Yanty Wirza (Edusentris, 2022)
Reflection on teachers’ teaching philosophy unveils underlying thoughts and perspectives behind every decision that teachers make in the classroom. However, studies focusing on examining experienced English teachers’ philosophy seem to be scant in the literature, especially in Indonesia context. Thus, this study aims at figuring out how experienced english teachers reflect on their teaching philosophy. The participants of this study were three experienced English teachers that were selected purposively. This qualitative study employed case study as its research design. the data were collected through semi-structured interviews and teachers’ journals and then were analyzed thematically. The findings of this study revealed that there were eight themes that emerged from the collected data, which were importance of english teaching at formal schooling; influence from beyond school life; the definition of teacher; how it is like to be an english teacher; the challenging aspects of teaching English; dealing with problems that occur during teaching English; adjusting the teaching practice; and teachers’ career critical incidents.